2019
DOI: 10.3390/jcm8122226
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Miro1 Cause Alterations of ER-Mitochondria Contact Sites in Fibroblasts from Parkinson’s Disease Patients

Abstract: Background: Although most cases of Parkinson´s disease (PD) are idiopathic with unknown cause, an increasing number of genes and genetic risk factors have been discovered that play a role in PD pathogenesis. Many of the PD-associated proteins are involved in mitochondrial quality control, e.g., PINK1, Parkin, and LRRK2, which were recently identified as regulators of mitochondrial-endoplasmic reticulum (ER) contact sites (MERCs) linking mitochondrial homeostasis to intracellular calcium handling. In this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 45 publications
8
44
2
Order By: Relevance
“…Our result also raises questions about whether PD is a systemic disease. In fact, mitochondrial molecular defects have been widely reported in fibroblasts from PD patients, 33‐37 but we have not observed skin cell death in PD patients. Why are dopaminergic neurons in the substantia nigra most vulnerable to the impairment of mitochondria?…”
Section: Miro1 Protein: a Linchpin For Mitochondrial Motility And Quacontrasting
confidence: 65%
“…Our result also raises questions about whether PD is a systemic disease. In fact, mitochondrial molecular defects have been widely reported in fibroblasts from PD patients, 33‐37 but we have not observed skin cell death in PD patients. Why are dopaminergic neurons in the substantia nigra most vulnerable to the impairment of mitochondria?…”
Section: Miro1 Protein: a Linchpin For Mitochondrial Motility And Quacontrasting
confidence: 65%
“…Very recently, four rare missense variants in RHOT1 were identi ed in PD patients from Caucasian populations. Using patient-derived broblasts, the researchers observed that these variants impaired calcium homeostasis and caused alterations of ER-mitochondria contact sites, ultimately affecting energy metabolism and increasing mitophagy [12,13]. The likely pathogenic variant identi ed in our study, p.S95N, is located in the N-GTPase domain, which is different from the location of the four reported variants.…”
Section: Discussioncontrasting
confidence: 60%
“…Importantly, heterozygous pathogenic variants in TRAP1 and HSPA9 were also found in PD patients [10,11]. Very recently, two studies on European ancestry found that mutation of ras homolog family member T1 (RHOT1), which encodes another pivotal mitochondrial transport protein (Miro1) and serves as mitochondrial-endoplasmic reticulum (ER) contact sites, also caused ADPD [12,13]. However, the role of the six Mendelian dominantly inherited mitochondrial function-associated genes is still awaiting con rmation or has not been duplicated in PD patients of different ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling of mitochondria, in turn, may impair the action of the fission machinery. As Miro is a substrate for Parkin(Wang et al, 2011; Shlevkov et al, 2016), and is itself a target of Parkinson’s Disease-associated mutations(Berenguer-Escuder et al, 2019), our results may also be relevant to pathogenetic mechanisms of Parkinson’s diseases.…”
Section: Resultsmentioning
confidence: 87%